Determination of Paleotsunami Inundation Zone Using Finite Difference Method in Southern Coastal Lebak, Banten - Muhammad Rizqy Septyandy; Shafira Selinzaskia Anwar (Jurnal Manajemen Bencana (JMB), 2023)
Paleotsunami deposits have been found in Indonesia, including in Pacitan, Kulon Progo, Cilacap, Pangandaran, and Sukabumi. This research aims to obtain an ideal model for determining the paleotsunami inundation zone along the southern coastal Lebak, Banten using finite difference numerical modeling through the MOST (Method of Splitting Tsunamis)-based ComMIT software. Field observations were made to identify the presence of paleotsunami deposits in the swale area on the southern coastal Lebak, Banten. Several tsunami scenarios such as Pangandaran in 2006, Indian Ocean Tsunami (IOT) in 2004, Tohoku in 2011, Sunda Strait megathrust segment, and megathrust along the south of Java were used in the modeling process to identify the characteristics of paleotsunami that were produced the tsunami deposits in the study area. Modeling is carried out using two schemes, such as using the ComMIT database unit source (subduction zone segments) and using the earthquake source parameters that are entered manually. The results show the best tsunami scenario that may have ever occurred in research area is the tsunami event with magnitude of 9.1 Mw, with maximum inundation range of 5.2 km, and run-off of up to 32 m, which is estimated as a tsunami event that precipates paleotsunami deposits in study area.